The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/lre.12339
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of vulnerable seagrass species Halophila beccarii Ascherson, 1871 from restored mangrove of Koduvally Estuary, south‐west coast of India

Abstract: The ocean turf grass, Halophila beccarii Ascherson, 1871 was recorded for the first time in the intertidal region of the restored mangrove ecosystem of the Koduvally Estuary on the south‐west coast of India. It was found co‐existing in the shallow muddy area of the mangroves, dominated by mangrove trees of Rhizophora mucronata and Sonneratia alba, and macroalgae, Ulva sp., Enteromorpha sp. and Chaetomorpha sp. The meadow is sparsely scattered with shoots near the mangroves, with a mean density of 720 shoots/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…(1) This study presents the first record of the overall distribution of H. beccarii along the coast of Hainan Lagoon in China, and we hope that this study will draw attention to the species. Although it has a rapid rate of rhizome elongation and a high seed yield to help with rapid recovery from disturbance, it is a pioneer species in mangrove formation, acting as a substrate stabilizer during the succession of mangroves [51]. However, it is only distributed in the intertidal zone where there is intensive man-made influence, so there is simply no way to deal with human activities such as aquaculture, destructive fishing, mangrove deforestation, agricultural, urban, and industrial wastewater discharges, oil spills, coastal construction, and waterway opening [2,20,23,24,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) This study presents the first record of the overall distribution of H. beccarii along the coast of Hainan Lagoon in China, and we hope that this study will draw attention to the species. Although it has a rapid rate of rhizome elongation and a high seed yield to help with rapid recovery from disturbance, it is a pioneer species in mangrove formation, acting as a substrate stabilizer during the succession of mangroves [51]. However, it is only distributed in the intertidal zone where there is intensive man-made influence, so there is simply no way to deal with human activities such as aquaculture, destructive fishing, mangrove deforestation, agricultural, urban, and industrial wastewater discharges, oil spills, coastal construction, and waterway opening [2,20,23,24,31].…”
Section: Discussionmentioning
confidence: 99%
“…Seagrass is mostly found in the low tidal zone, 0.9-1.5 m above sea level [14], with maximum depths of 1 m and 1.7 m on the west and east coasts of India, respectively [4]. It has a wide salinity tolerance, survives, and continues to reproduce at salinities of 0-45 [14,[51][52][53]. In contrast, this study found that the water depth of the H. beccarii habitat in Hainan was 0.3-2.3 m, while no seagrass was found deeper than 2.6 m. The salinity range of 9.6-33.96 was consistent with the salinity of seagrass habitat in general, i.e., 16-35 [7].…”
Section: Water Environmentmentioning
confidence: 99%
“…However new areas with seagrass presence are becoming evident, such as the recent report of H. beccarii from the coast of Kerala (Prabhakaran et al, 2020). However, due to increasing human-induced disturbances and coastal developments, the seagrass beds of India are under decline (Kaladharan et al, 2013;Mishra & Apte, 2020.…”
Section: Introductionmentioning
confidence: 99%